Patellar Transskeletal Traction for the Treatment of Chronic Patellar Pseudoarthrosis - José Leonardo Rocha de Faria; Dieno Mol Souza Portella; Victor Elias Titonelli; Naasson Trindade Cavanellas; Rodrigo Pires e Albuquerque; Eduardo Branco de Sousa; João Maurício Barretto (Case Reports in Orthopedics)
Patellar fractures, which constitute approximately 1% of bone lesions, may lead to severe impairment of the extensor mechanism. When conservative or surgical treatment fails, the patella may develop pseudoarthrosis. Neglect or delayed treatment of this type of injury may lead to significant diastasis between the patellar fragments. There is no consensus regarding the best treatment for such cases. This study is aimed at describing a rare case of patellar pseudoarthrosis in a patient who underwent two-step surgical treatment comprising transskeletal patellar traction followed by osteosynthesis with a tension band. A 17-year-old male patient presented with a left patellar fracture that resulted from a fall from a standing height 8 years ago. He did not undergo any type of surgical treatment during that time, but the fracture was immobilized for only 2 weeks. The two-step surgical treatment with transskeletal patellar traction and patellar osteosynthesis was performed and provided satisfactory functional clinical results in this patient. This two-step surgical treatment can be performed in cases similar to ours with satisfactory results.